Kesulitan Konsentrasi Siswa dalam Belajar Bahasa Indonesia: Studi Kasus Kelas V SDN 131/II SKB - Fitria Rahmadani; Apdoludin Apdoludin; Dedek Helida Pitra (Master Qualitative Research in Education, 2025)
Difficulty in concentration is an obstacle experienced by students when focusing their attention on learning materials. This study was motivated by the noticeable learning concentration problems in Indonesian language lessons. The research aims to describe students’ learning concentration difficulties in Indonesian subjects, the factors influencing these difficulties, and the teachers’ efforts to overcome them. The research method employed was a case study with a qualitative approach. The study was conducted at SDN 131/II SKB from January to July with five fifth-grade students as research subjects, selected based on students’ habitual criteria and recommendations from the homeroom teacher. Data were collected through observation, interviews, and documentation. The findings indicate that fifth-grade students at SDN 131/II SKB demonstrate uneven concentration in Indonesian language learning, as observed in their cognitive, affective, and psychomotor behaviors during the learning process. Supporting factors for students’ learning concentration include healthy physical conditions, engaging teaching methods, and non-coercive learning environments that make students feel more comfortable. Meanwhile, the factors contributing to concentration difficulties are lack of interest in the subject matter, fatigue, medical history, limited variation in teaching methods, unconducive learning environments, and peer influence. Teachers’ efforts to overcome these difficulties include recognizing students’ individual characteristics, applying the concept of reward and punishment, and fostering better study habits.